GENDER APPROACH IN MONITORING STUDIES OF PUPILS’ IC-COMPETENCE IN EDUCATIONAL PRACTICE IN EUROPE - Olena O. Hrytsenchuk (Information technologies and learning tools, 2013)
The article deals with the analysis of gender issues in monitoring studies of students’ information and communication competence ( IC-competencies) in european secondary schools at the present stage. There are highlighted the results of research of experience of international organizations, such as: UNDP, UNESCO, UNІSEF, The International Association for the Evaluation of Educational Achievement – IEA, Organisation for Economic Co-operation and Development – OECD) on monitoring studies of students’ IC-competencies. There are identified peculiarities, common trends and future development.